EnglishScore app practices: fostering EFL students’ listening skills through English test - Azizah Maulina Erzad; Suciati (Erudita: Journal of English Language Teaching, 2024)
Listening is one of the English skills that EFL students struggle with. Various English listening audio can be used as listening materials. However, doing a listening test can be an alternative to enhance listening skills. This study highlights how the EnglishScore app affects listening skills and the benefits and drawbacks of using it. A qualitative study was conducted in this research. Eighty-four EFL students who took the listening subject filled out an open-ended questionnaire using Google Forms to collect the data. Observation and documentation were also used as data collection techniques. The research findings revealed that the students practiced using the EnglishScore app at least twice to know their improvements. Most participants acknowledged that they had a good impact on their listening skills. This app provided benefits by providing various listening materials, training the students to become autonomous learners, and managing their time well. Meanwhile, the drawbacks were that there needed to be corrections or feedback, including the potential for technical problems and the need for accommodating different learning styles or the diverse proficiency levels in the classroom.